2017
DOI: 10.3390/ma10050501
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Silicate/Chitosan-Coated Electrospun Poly (Lactic Acid) Fibers for Bone Tissue Engineering

Abstract: Electrospinning technology allows fabrication of nano- or microfibrous fibers with inorganic and organic matrix and it is widely applied in bone tissue engineering as it allows precise control over the shapes and structures of the fibers. Natural bone has an ordered composition of organic fibers with dispersion of inorganic apatite among them. In this study, poly (lactic acid) (PLA) mats were fabricated with electrospinning and coated with chitosan (CH)/calcium silicate (CS) mixer. The microstructure, chemical… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…Wettability plays a key role in determining the biological behavior of a biomaterial, and thus is a critical factor when designing biomaterials 30 . Cellular behaviors were enhanced when cells were grown on specimens with a water contact angle that was lower than 75° 31 . Our data further indicated that gelatin-BVSM materials were hydrophilic 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Wettability plays a key role in determining the biological behavior of a biomaterial, and thus is a critical factor when designing biomaterials 30 . Cellular behaviors were enhanced when cells were grown on specimens with a water contact angle that was lower than 75° 31 . Our data further indicated that gelatin-BVSM materials were hydrophilic 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Altering manufacturing parameters makes it possible for stimulating natural tissues with tailored biological characteristics appropriate for the recovery of tissues. The advantages of CS are actually broadly described; among the major positive aspects of CS, one can mention the capability to modify properties such as the degradation rate by altering the degree of deacetylation and it's Mw [157][158][159][160][161][162][163][164][165][166][167][168]. Additive components are regularly incorporated into CS in an effort to enhance its printability, fidelity, or to fabricate new cell-laden matrices.…”
Section: Benefits Limitations and Future Prospectsmentioning
confidence: 99%
“…It is observed that the zein/HA membranes can support cell proliferation and shows promise in bone tissue engineering applications. Su et al [148] studied the secretion levels of Collagen I and fibronectin on electrospun PLA NFs coated by calcium silicate. They found that using inorganic apatite coatings tend to make suitable conditions for bone tissue engineering.…”
Section: Applications Of Ceramic Electrospun Matsmentioning
confidence: 99%